2014
DOI: 10.1128/jcm.02140-14
|View full text |Cite
|
Sign up to set email alerts
|

Improved Diagnosis of Infection Associated with Osteosynthesis by Use of Sonication of Fracture Fixation Implants

Abstract: Previous studies have shown that sonication fluid cultures from removed orthopedic devices improved the microbiological diagnosis of orthopedic implant-associated infections; however, few of these investigations have applied sonication to the removed fracture fixation devices to evaluate its utility for the diagnosis of osteosynthesis-associated infection (OAI). We compared sonication fluid to conventional tissue cultures from 180 subjects with different sizes of plates and screws (n ‫؍‬ 156), spinal implants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
87
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 30 publications
1
87
1
4
Order By: Relevance
“…Previous studies have shown that liquid cultures seem to provide better conditions to sessile bacterial growth than solid media (9,10). As already shown in previous studies addressing OIAI and prosthetic joint infection, Gram-positive bacteria were the most common sessile pathogens isolated in SC (60.6%) and SMF (72.7%), followed by Gram-negative bacilli, which have been increasingly identified among subjects presenting OIAIs (3,11). Our study had limitations, including the small sample size analyzed and the lack of a universally accepted clinical diagnosis of OIAI.…”
mentioning
confidence: 50%
See 4 more Smart Citations
“…Previous studies have shown that liquid cultures seem to provide better conditions to sessile bacterial growth than solid media (9,10). As already shown in previous studies addressing OIAI and prosthetic joint infection, Gram-positive bacteria were the most common sessile pathogens isolated in SC (60.6%) and SMF (72.7%), followed by Gram-negative bacilli, which have been increasingly identified among subjects presenting OIAIs (3,11). Our study had limitations, including the small sample size analyzed and the lack of a universally accepted clinical diagnosis of OIAI.…”
mentioning
confidence: 50%
“…everal authors have applied a sonication technique as an adjunctive diagnostic tool to increase the identification of causative agents of different orthopedic implant-associated infections (OIAIs) (1)(2)(3). However, sonication may also give false-negative results in at least 10% to 20% of cases when applying only phenotypic methods (4).…”
mentioning
confidence: 99%
See 3 more Smart Citations